Heat exchange in molten pool in liquid-phase melting of ore-coal pellets - Kostyakov, V.N.; Poletaev, E.B.; Grigorenko, G.M.; Medved, S.N.; Shevchuk, E.A.; Yasinsky, A.A.; Yakovishin, O.A. (Современная электрометаллургия, 2008)
Results of the heat exchange investigation in a pool in liquid-phase melting of the ore-coal pellets are presented. Dependence of heat-transfer coefficient from the slag to a pellet upon intensity of the slag mixing in the furnace pool is established.